Health, Physical Activity and Musculoskeletal Symptoms among Stone, Sand, and Gravel Mine Workers: Implications for Enhancing and Sustaining Worker Health and Safety - Todd D. Smith; Abdulrazak O. Balogun; Zuojin Yu; Charmaine Mullins-Jaime (Safety, 2020)
There is little data delineating relationships between health and worker musculoskeletal symptoms (MSS), particularly among stone, sand, and gravel mine (SSGM) workers. There is also little data detailing the relationships between physical activity and MSS among these workers. A cross-sectional study using data from 459 SSGM workers was completed. Logistic regression analyses assessed relationships between health factors, physical activity, and low back, neck, shoulder, and knee MSS. Those who reported their health as very good/excellent were less likely to suffer low back and knee MSS. Those who indicated their health was poor/fair were more likely to suffer shoulder, neck, and knee MSS. Obese workers were more likely to experience knee MSS and those who smoked in the past had higher odds of neck MSS. Vigorous physical activity was mostly protective, but those performing more than 5 h of moderate physical activity each week had greater odds of shoulder and neck MSS. Given these results, workers in SSGM may benefit from targeted interventions that bolster vigorous physical activity and improve health. Further, health protection efforts need to be initiated by SSGM operations to address work issues and to sustain health as job roles and work hours impacted MSS as well.